Comparison of Video Tutorials and PowerPoint on Microsoft Project Learning Outcomes in Vocational High School - Chika Restyanty Maha Dewi Putri; Muhammad Kris Yuan Hidayatulloh; Gde Agus Yudha Prawira Adistana; Desy Ratna Arthaningtyas (CV. Edujavare Publishing, 2026)
Advances in digital technology have had an impact on various aspects of life, including education. This study examines differences in students’ learning outcomes between the use of video tutorial and PowerPoint media in Microsoft Project learning at a vocational high school. A quantitative approach with a quasi-experimental nonequivalent control group design was applied, involving two intact classes consisting of 30 students in each group. Data were collected through pretests, posttests, and student response questionnaires, and analyzed using descriptive statistics and a Mann-Whitney U test. The results show that the video tutorial group obtained a higher mean score (82.53) compared to the PowerPoint group (71.27). The hypothesis test also indicated a significant difference between the two groups with a significance value of 0.000 (<0.05). In addition, students gave very positive responses to the video tutorial media, with a percentage of 84.6%. These findings indicate that different learning media are associated with different learning outcomes in Microsoft Project instruction.